USING THE MAPLE COMPUTER MATHEMATICS SYSTEM TO PROVE THE LAW OF ORTHOGONALITY OF THE MATRICES OF DIRECT AND INVERSE TRANSFORMATIONS COMPOSED BY V. Z. VLASOV - Ovskiy, A. G.; Tolok, V. A. (Radio Electronics, Computer Science, Control, 2024)
Authors analyse got Vlasov V. Z. [1] general statement decision of freedimension equations of theory of resiliency, check up his basic properties in the system of programming of Maple. Law of ortogonal of matrices of direct and reverse transformations, made in obedience to work of Vlasov V. Z. is proved in the developed program. A simplifying symbolic record as transcendent operating formulas, which allows to apply COMPUTER for the construction of mathematical models of tasks of theory of resiliency, is in-process utillized.